Research on the Teaching of Visual Communication Design Based on Digital Technology - Jianying Bian (Hindawi-Wiley, 2021)
In the era of big data, the rapid development of information technology has made the sharing of data and information more free, bringing convenience to the public, but at the same time, the massive amount of data also brings “information anxiety.” In this paper, we use the knowledge of design discipline, combined with psychological cognitive science, statistics, and communication discipline, and analyze a large number of excellent cases to effectively combine “information visualization-visual representation-design.” The purpose of this study is to enable audiences to efficiently access information through visual symbols in a large amount of data and to increase their interest in reading and satisfaction in accessing information. As a carrier of communication between designers and audiences in the process of visual representation of information visualization, visual symbols can effectively convey information content and emotional concepts to audiences. Finally, based on the theoretical support of the previous paper, combined with our own practical experience, we conduct a systematic study on the application of design thinking and the construction of design methods for the design of visual representations of information visualization. A comparative study on the aesthetics of different categories of APP interface design is conducted, and it is believed that different categories of APP can create distinctive and different categories of APP interface aesthetics through the differentiated design of interface layout, content expression, and visual form, which is considered as the ultimate goal that APP interface design must pursue. Visual representation is a method and means to realize information visualization as a representation practice that expresses the meaning of information in the form of visual symbols. The visual representation of information visualization uses visual symbols as a medium, and the audience interprets the visual symbols based on cognitive experience to obtain information, which helps to maximize the dissemination of information.